2020
DOI: 10.1017/s1049096520000888
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the Military and Revolutions: Simulating Civil–Military Relations during Mass Uprisings

Abstract: During revolutions, strategic interactions among civilian policy makers, armed forces, and opposition groups shape political outcomes—most important, whether a regime stands or falls. Students from advanced industrial democracies frequently find these dynamics counterintuitive, even after completing readings and engaging in traditional instruction methods. We therefore sought to improve pedagogical outcomes by designing a simulation based on scenarios similar to those witnessed during the Arab Spring and Ukrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Simulations-e.g., of earthquakes, investment risks, and old age-can provide tangible demonstrations of the impact of potential risks without exposing individuals to actual harm (Hertwig & Wulff, 2022). Available simulations like the Swiss Seismological Service's Earthquake Games 3 or role-playing simulations on transitions to democracy (Jiménez, 2015) or civil-military relations during mass uprisings (Harkness & DeVore, 2021) vaccination found that people exposed to an interactive risk-ratio simulation were more likely to get vaccinated and tend to have a better understanding of the benefit-to-harm ratio (Wegwarth et al, 2023) than people presented with the same information in a conventional text-based format. It is difficult to directly target elites with interventions;…”
Section: Arresting Democratic Backsliding 22mentioning
confidence: 99%
“…Simulations-e.g., of earthquakes, investment risks, and old age-can provide tangible demonstrations of the impact of potential risks without exposing individuals to actual harm (Hertwig & Wulff, 2022). Available simulations like the Swiss Seismological Service's Earthquake Games 3 or role-playing simulations on transitions to democracy (Jiménez, 2015) or civil-military relations during mass uprisings (Harkness & DeVore, 2021) vaccination found that people exposed to an interactive risk-ratio simulation were more likely to get vaccinated and tend to have a better understanding of the benefit-to-harm ratio (Wegwarth et al, 2023) than people presented with the same information in a conventional text-based format. It is difficult to directly target elites with interventions;…”
Section: Arresting Democratic Backsliding 22mentioning
confidence: 99%
“…Mello and Stein (2021) linked two courses in which students designed multiple simulations based on historical protests. Harkness and DeVore (2021) created a fictional scenario for their two-hour simulation session on revolution, providing their students with information on roles and rules one week in advance. Jimenez (2015) limited student collaboration to emphasize the coordinating costs of rebellions.…”
Section: Simulations and Active Learningmentioning
confidence: 99%
“…This article describes a case study of a simulation embedded in a course titled “The Police and Social Movements in American Politics” that was taught in 2021 in the Politics Department at Brandeis University. Scholars have found that simulations can provide students with a more intense engagement with and a deeper understanding of real-world actors’ motivations and strategies (Harkness and DeVore 2021). We created a semifictional future scenario because when students simply replicate a well-known past event, they tend to “tailor their actions to reflect what actually happened or to their preconceived prejudices” (Harkness and DeVore 2021, 317).…”
mentioning
confidence: 99%
See 1 more Smart Citation